2014
DOI: 10.1242/dev.106211
|View full text |Cite
|
Sign up to set email alerts
|

A conserved axon type hierarchy governing peripheral nerve assembly

Abstract: In gnathostome vertebrates, including fish, birds and mammals, peripheral nerves link nervous system, body and immediate environment by integrating efferent pathways controlling movement apparatus or organ function and afferent pathways underlying somatosensation. Several lines of evidence suggest that peripheral nerve assembly involves instructive interactions between efferent and afferent axon types, but conflicting findings challenge this view. Using genetic modeling in zebrafish, chick and mouse we uncover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…In fish, birds, and mammals, peripheral nerves are not only composed of afferent sensory axons but also include efferent pathways controlling diverse aspects of peripheral organ function. In this work, we did not focus on the relationship between afferent and efferent axons during peripheral nerve regeneration, as it has been shown that sensory efferent projections rely for growth on their association with pre-formed sensory afferent trajectories [ 79 ]. These authors also showed that this relationship between both types of axons is preserved from fish to mammals.…”
Section: Discussionmentioning
confidence: 99%
“…In fish, birds, and mammals, peripheral nerves are not only composed of afferent sensory axons but also include efferent pathways controlling diverse aspects of peripheral organ function. In this work, we did not focus on the relationship between afferent and efferent axons during peripheral nerve regeneration, as it has been shown that sensory efferent projections rely for growth on their association with pre-formed sensory afferent trajectories [ 79 ]. These authors also showed that this relationship between both types of axons is preserved from fish to mammals.…”
Section: Discussionmentioning
confidence: 99%
“…The motor neural networks were the first to evolve, followed by the sensory and autonomic [84]. All vertebrates have a well-developed motor network.…”
Section: Innervation Of the Skeleton—overviewmentioning
confidence: 99%
“…From Wang et al (2014), where further details may be found. Axons forming the dorsal primary ramus (dr) branch off toward the epimere (epaxial muscle) at E10.5.…”
Section: The Formation Of Motor Columnsmentioning
confidence: 99%